Infographic Design of Flow/Procedure of MBKM Guide Universitas Pembangunan Nasional “Veteran” Jawa Timur - Sri Suryani Yuprapti Winasih; Widyasari; Aninditya Daniar; Muhammad Raihan Iqbal; Aisya Jasmine Defina (Nusantara Science and Technology Proceedings, 2022)
The Independent Learning Campus Independent Policy (MBKM) in the world of education is a breakthrough by government to bring the world of work closer to the world of education. The MBKM learning model encourages student to be mopre adaptive in facing the world of work that demands competencies and abilities from various diciplines. To implement the MBKM program, Higher Education (PT) prepares implementation guidelines for student. The implementation MBKM activity guide book will be easy to understand if it uses effective and communicative language, for that aguide book is needed that is prepared in the form of flow/procedure infographic design. Infographics are text-shaped information media with a combination of image, graphics ilustrations and typography so that it s more attractive and easier to understand. Faculty Excellence Product Research entitled Infographic Booklet for MBKM Guide” aim to make easier for student to understand the content of procedures for implementating MBKM activities. The methods and steps for compiling infografics booklet consist of the pre-production stage, namely collecting and managing MBKM guide data information and documenting library sources about infographics. Next is the production stage, which is determining the type of information and visual design using infographic techniques packaged in the form of booklet. Finally the post production stage, namely the finishing of the MBKM guide booklert which is printed and distributed to the entire acedemic community in the form of hardcopy and softcopies uploaded on the UPN “Veteran” Jawa Timur website.